Pemanfaatan Umbi Gembili Sebagai Alternatif Kemandirian Pangan dan Ekonomi Warga Desa Bangunjiwo, Kecamatan Kasihan, Bantul - Darmawan, Rivaldi; Nurudin, Muhammad Fatwa; Utami, Dinar Dewi; Fatmawati, Tria Ayu; Rosyada, Pani Amrina; As'ad, Syarif; Asri Suwarsi, Aqidah (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
Gembili (Dioscorea esculenta) is a type of tuber that thrives in tropical climates. The high carbohydrate content makes people in some parts of Indonesia use it as a staple food substitute for rice. However, because there are not many processed variations produced by this plant, it makes the public's interest in cultivating this plant low. This is because there are no new innovations known to the public in the use of this plant. For this reason, the BEM FAI UMY community empowerment team saw a great opportunity from this Gembili plant to be managed to produce processed food products that could have high economic value. One of the advantages of this plant is the content of the elements disocorin and inulin which makes gembili flour has the advantage of being low in sugar. The purpose of this program is to increase food self-sufficiency and the local economy by utilizing Gembili plants which are commonly found in Bangunjiwo village, Kasihan Bantul. In addition, this program provides an alternative business for the community to increase independence in gembili management and to form a joint business group (KUB) in Padukuhan Kenalan. The method used is to provide training and assistance in making gembili noodles both in the manufacturing, production and marketing processes. The results of this service itself are: (1) increasing public knowledge about gembili management so that it is managed more usefully (2) Realizing a Joint Business Group (KUB) that can improve the welfare of the Padukuhan Kenalan community.